1976
DOI: 10.1002/oms.1210110216
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis, methanolysis and ammonolysis of dicarboxylic acids and methyl esters under conditions of chemical ionization mass spectrometry

Abstract: Chemical ionization mass spectra of dicarboxylic acids and methyl esters show fragmentation and unimolecular reactions with reagent gases water, methanol, ammonia and methyl ether, which differ from those observed with hydrocarbon reagents methane and isobutane. These reactions involve exchange of the reagent gas for water or methanol of the dicarboxyl compounds, as well as secondary exchange of both functions. An effort has been made to determine the mechanism of these reactions and to determine the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…In order to maintain a tolerable working pressure in the source, a high pumping speed is required, which results in most of the desired ions generated in the source passing with the main flow into the pump and only about 1% of them passing through the ion exit hole into the analyzer region. One would like to increase the efficiency of the source, and Lewis, Smith, and Veares (6) found that a positively biased electrode placed slightly downstream from the ion exit hole increased meaningfully the intensity of the mass spectra. In addition, they noted remarkable qualitative changes occurring at higher electrode potentials in that the relative intensities of low-mass…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain a tolerable working pressure in the source, a high pumping speed is required, which results in most of the desired ions generated in the source passing with the main flow into the pump and only about 1% of them passing through the ion exit hole into the analyzer region. One would like to increase the efficiency of the source, and Lewis, Smith, and Veares (6) found that a positively biased electrode placed slightly downstream from the ion exit hole increased meaningfully the intensity of the mass spectra. In addition, they noted remarkable qualitative changes occurring at higher electrode potentials in that the relative intensities of low-mass…”
Section: Resultsmentioning
confidence: 99%
“…Positive ion chemical ionization mass spectra using proton-transfer reagents are not ideally suited for the analysis either, since the spectra of underivatized acids generally exhibit the (MH -H20)+ fragment ions indicative of the loss of water from the protonated molecular ions (6). These fragment ions also complicate the molecular weight determinations and the identification of acid types.…”
Section: Determination Of Naphthenic Acids In California Crudes and R...mentioning
confidence: 99%
“…In the methane-CI mode, a distinct quasi-molecular ion [MH] and a [M+C2H5] adduct are present, and the base peak of dicarboxylic acid methyl esters is the [MH-CH3OH] fragment (17). Fatty acids also give [MH-CH3OH] fragments but at higher m/e values.…”
Section: Resultsmentioning
confidence: 99%
“…Η απώλεια ενός μορίου H 2 O από το πρωτονιομένο μοριακό ιόν, έχει αναφερθεί ξανά στην περίπτωση του πινονικού οξέος κατά την ανάλυσή του σε μεθανικό χημικό ιονισμό (Christoffersen et al, 1998). + και [ΜΝΗ 4 -64] + , αλλά και η σχετικά υψηλή αναλογία του [ΜΗ] + , υποδεικνύουν έναν μηχανισμό παρόμοιο με αυτόν που έχει αναφερθεί σε άλλες μελέτες(Weinkam and Gal, 1976b;Westmore and Alauddin, 1986). Τα παραπάνω είναι πιθανόν να πραγματοποιούνται μέσω ενδιαμέσων που περιλαμβάνουν το άνοιγμα του τετραμελούς δακτυλίου.…”
unclassified